PERBANDINGAN ANTARA PEMBERIAN ANTIBIOTIKA MONOTERAPI DENGAN DUALTERAPI TERHADAP OUTCOME PADA PASIEN COMMUNITY ACQUIRED PNEUMONIA (CAP) DI RUMAH SAKIT SANGLAH DENPASAR - Sajinadiyasa, I GK; Ngurah Rai, IB; Sriyeni, LG (journal of internal medicine; Vol. 12, No. 1 Januari 2011)
Among CAP patient, there are still some controversies about eÞ cacy of various approach management for the patient. There are important issues about using the dual therapy improving the better outcome compared to monotherapy of CAP patient. A retrospective study was held on CAP patients, who were hospitalized in Sanglah Hospital in 2008-2009 to compare between dual versus monotherapy antibiotic with the outcome. Seventy Þ ve subjects were included in this study. About 73.3% subjects received dual therapy (cefotaxim and azitromicyn) and 26.7% received monotherapy (levoß oxacin). There were no signiÞ cant correlation between dual vs monotherapy antibiotic with length of stay (LOS) (p = 0.075) or with mortality (p = 0.367). Also there were no correlation between PSI score and LOS (p = 0.303) and mortality (p = 1.000). In age group, there was signiÞ cant correlation between age and mortality (p = 0.025), but there were no signiÞ cant correlation with LOS (p = 0.265). As our conclusions, we Þ nd there were no signiÞ cant correlation between dual vs monotherapy antibiotic with outcome patient CAP. But there was signiÞ cant correlation about patient in older age had higher mortality compare with younger age.
Keywords: community-acquired pneumonia, mono vs dual antibiotic therapy